Peranan ITX Sebagai E-Marketplace di Kawasan Danau Toba - Ina Veronika Ginting; Wisnu Prahadianto; Dwiesty Dyah Utami; Nuniek Agatri; Delanita Fachrunisa (Tourism Scientific Journal, 2020)
Lake Toba area has the potential in the field of tourism business that is useful for the businessman. In order to achieve the target of 1 million tourists targeted by the Badan Pelaksana Otorita Danau Toba required a media marketing role that is able to support it. One of its marketing efforts is through ITX (Indonesia Tourism Exchange) which can develop the business network of tourism so that tourism business products become better known globally, easier booking process and online payment transactions to be more efficient and reliable. Asdep Tata Kelola Destinasi dan Pemberdayaan Masyarakat, held socialization in Tobasa district. After the socialization, tourism businessmen who join to become ITX members are Polado Homestay and CV. Toba Sporty from 30 participants. Obviously after becoming a member of ITX, the businessmen who have joined must have changes. Therefore it is necessary to conduct research on the role of ITX as an e-marketplace in Lake Toba area. In this study the researchers used qualitative descriptive research methods. This research uses e-marketplace theory. Data collection techniques used interviews and documentation. The whole study yields a conclusion and suggestion related to the role of ITX.